The Impacts of Story-retelling Activities on the Kindergartener’s Activation of the Communication Strategies - Retnowati, Nanik; Rejeki, Sri; Indah, Yani Awalia; Anwar, Husnul Bidayah; Rahayu, Eka Pamuji (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Many experts undeniably acknowledge the effectiveness of story-retelling activities in improving many aspects of learning. This case study investigates how story-retelling activity impacts the student’s communication strategy. The study involved a teacher and a five-year-old student at an Islamic kindergarten. Data was gathered through direct observation and interviews. The teacher’s activity in telling a story and the student’s retelling activity were recorded. Then, the utterances produced by the teacher and the student were transcribed and compared based on the SNAP procedure proposed by Strong. The assessment had four criteria: story length, error type, comprehension type, and story grammar. The assessment explained to what extent the student understood the story told by the teacher. With his understanding, the student struggled to deliver the story using a communication strategy. It was found that the student’s story length was 27% of the teacher’s story length. He made four types of errors, performed 83% factual type comprehension, fulfilled all components in the story grammar, and applied both avoidance and compensatory communication strategies. The results of research data analysis show that retelling activities have triggered the implementation of communication. From a language education perspective, communication strategy is part of communicative competence.